2012
DOI: 10.2304/gsch.2012.2.2.97
|View full text |Cite
|
Sign up to set email alerts
|

A Case for Using Indigenous Children's Literature for Emotion Socialization in Schools

Abstract: Building on the work of developmental theorists, this article argues that school is a significant cultural site for emotion socialization and that the use of cultural texts such as children's picture books can play an important role in helping young children to identify and express emotions, and learn about their relational context. The author takes the perspective that teaching and learning about emotions are never neutral; they are complex, dialectical and are freighted by history, relations of power and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…For example, research (McNeil, 2012) that focused on the Métis people, an underrepresented Indigenous people of Saskatchewan, suggested that the inclusion of related, authentic texts is critical because, "books can be used to engender appreciation of the family and cultural contexts of emotion socialization in Métis families" (p. 104). Further these and similar related texts must be used "to counter…racially and culturally exclusionary practices in the area of children's texts" (p. 98).…”
Section: High Quality Authentic Children's Multicultural Literaturementioning
confidence: 99%
“…For example, research (McNeil, 2012) that focused on the Métis people, an underrepresented Indigenous people of Saskatchewan, suggested that the inclusion of related, authentic texts is critical because, "books can be used to engender appreciation of the family and cultural contexts of emotion socialization in Métis families" (p. 104). Further these and similar related texts must be used "to counter…racially and culturally exclusionary practices in the area of children's texts" (p. 98).…”
Section: High Quality Authentic Children's Multicultural Literaturementioning
confidence: 99%